Feasibility of NaF PET/CT and MRI for Noninvasive In Vivo Quantification of Knee Pathophysiological Bone Metabolism in a Canine Model of Post-traumatic Osteoarthritis - Maria I. Menendez DVM, PhD; Bianca Hettlich DrMedVet; Lai Wei PhD; Michael V. Knopp MD, PhD (Molecular Imaging)
Purpose: To assess and quantify by molecular imaging knee osseous metabolic changes serially in an in vivo canine model of posttraumatic osteoarthritis (PTOA) of the knee utilizing sodium fluoride (Na 18 F) positron emission tomography (PET)/computed tomography (CT) coregistered with magnetic resonance imaging (MRI). Materials and Methods: Sodium fluoride PET imaging of 5 canines was performed prior to anterior cruciate ligament transection (ACLT) and 2 times post-ACLT (3 and 12 weeks). The PET/CT was coregistered with MRI, enabling serial anatomically guided visual and quantitative three-dimensional (3D) region of interest (ROI) assessment by maximum standardized uptake value. Results: Prior to ACLT, every 3D ROI assessed in both knees showed no Na 18 F uptake above background. The uptake of Na 18 F in the bone of the ACLT knees increased exponentially, presenting significantly higher uptake at 12 weeks in every region compared to the ACLT knees at baseline. Furthermore, the uninjured contralateral limb and the ipsilateral distal bones and joints presented Na 18 F uptake at 3 and 12 weeks post-ACLT. Conclusion: This study demonstrated that Na 18 F PET/CT coregistered with MRI is a feasible molecular imaging biomarker to assess knee osseous metabolic changes serially in an in vivo canine model of knee PTOA. Moreover, it brings a novel musculoskeletal preclinical imaging methodology that can provide unique insights into PTOA pathophysiology.